Bractwa religijne w epoce staropolskiej w świetle ich organizacji i struktury wewnętrznej - Flaga, Jerzy (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The internal structure of the religious fraternities shows that it was, if not exemplary, certainly well thought out and carried out with full awareness. It reflects well on fraternities, even though they were very common organizations and had a large number of people with different social status as well as educational and intellectual levels, because they were open to all those willing to join them. Perhaps that is why, in addition to the devotional and religious reasons given by the Church, they were so commonplace. All of this undoubtedly affected the role that fraternities, or more broadly, religious associations played in the history of the Church, the entire societies and local communities of those times.